Wage-productivity gap in OECD economies - Ceyhun Elgin; Tolga Umut Kuzubas (Kiel Institute for the World Economy (IfW), 2013)
The Walrasian theory of labor market equilibrium predicts that in the absence of any market frictions, workers earn a wage rate equal to their marginal productivity. However, this observation is not supported empirically for various economies. Based on the neoclassical tradition, the ratio of the marginal product of labor to real wages is generally defined as the Pigouvian exploitation rate. In this paper, the authors calculate this specific wage-productivity gap for the manufacturing sector in OECD economies and investigate its relation to the unemployment rate along with other variables such as government taxation, capital expansion, unionization, inflation. The authors find that the wage productivity gap gives a robust and significantly positive response to shocks to the unemployment rate and negative response to shocks to unionization.
Keywords: J24; J30; J64; 330; wages; marginal productivity of labor; panel-VAR; OECD economies